2021
DOI: 10.1186/s12940-021-00691-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of acute kidney injury in a tertiary hospital academic center: an observational cohort study

Abstract: Background The aim of our study was to describe seasonal trends of acute kidney injury (AKI) and its relationship with weather conditions in a hospitalized population. Methods We retrospectively collected demographic (age, sex), clinical (ICD-9-CM codes of diagnosis discharge) and laboratory data (creatinine values) from the inpatient population admitted to Fondazione Policlinico Universitario A. Gemelli IRCCS between January 2010 and December 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
2
10
1
1
Order By: Relevance
“…Also 30-day mortality was higher in winter months. Similar results were highlighted in an Italian hospital setting, underlining how winter was associated with increased risk of AKI and that low air temperature and high relative humidity increased the risk of AKI [16].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Also 30-day mortality was higher in winter months. Similar results were highlighted in an Italian hospital setting, underlining how winter was associated with increased risk of AKI and that low air temperature and high relative humidity increased the risk of AKI [16].…”
Section: Discussionsupporting
confidence: 78%
“…Several epidemiological studies have reported a seasonal trend in different clinical conditions in the surgical [3], traumatological [4] and medical [5] fields, in particular cardiovascular [6][7][8][9][10][11][12], respiratory [13] and infectious illness [14] have got a winter peak in their frequency. Also, acute kidney injury (AKI) has been described to have an incidence peak during winter [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The most common etiological factors were prerenal followed by sepsis, ischemic acute tubular necrosis [12]. Lombardy et al [13] studied causes of AKI in 2864 patients. They reported that AKI was more period in winter period (RR: 1.16; 95% CI: 1.05-1.29; p = 0.003) and AKI risk was found to be associated with lower air temperature and higher humidity [13].…”
Section: Discussionmentioning
confidence: 99%
“…Lombardy et al [13] studied causes of AKI in 2864 patients. They reported that AKI was more period in winter period (RR: 1.16; 95% CI: 1.05-1.29; p = 0.003) and AKI risk was found to be associated with lower air temperature and higher humidity [13]. In our study, the most frequent cause of prerenal AKI was dehydration, heart failure and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a severe pathological condition often observed in the hospitalized population [1, 2]. The reported incidence is quite variable, ranging from 7% to 57% [3, 4].…”
Section: Introductionmentioning
confidence: 99%